Point-contact Andreev reflection spectroscopy of a magnetic superconductor Dy0.6Y0.4Rh3.85Ru0.15B4 - Rybaltchenko, L.F.; Khristenko, E.V.; Ishchenko, L.A.; Terekhov, A.V.; Zolochevskii, I.V.; Salenkova, T.V.; Khlybov, E.P.; Zaleski, A.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The Andreev reflection spectra dI/dV(V) of the magnetic superconductor Dy0.6Y0.4Rh3.85Ru0.15B4 have been investigated. Pronounced stimulation of superconductivity by an external magnetic field has been observed for the first time. The effect showed up as enhancement of the gap structure (and hence the gap itself) in the spectra and its shift towards higher voltages with an increasing field. In the intermediate fields the structure also behaved strangely: instead of the usual smooth decrease with a grooving field, the gap features dropped abruptly near the critical point Hc2. Of interest is also the abnormally high relative gap value 2Δ/kBTc ≈ 4 (as compared to conventional singlet superconductors) which was found for some contacts from a comparison of experimental spectra and the modified Blonder–Tinkham–Klapwiyk theory. We attribute the features revealed in the point-contact spectroscopic investigations of Dy0.6Y0.4Rh3.85Ru0.15B4 in a magnetic field to the triplet-type Cooper pairing in the compound because only in this case one can expect the stimulation of superconductivity in the stationary magnetic fields up to 0.7Hc2.